The Impact of Macroeconomics on the Performance of the Indonesian Sharia Stock Index: A Comprehensive Analysis - Faizi, Faizi; Anggoro, Muhammar Dinda Fahlepi Anggoro (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
Unstable fluctuations in the Indonesian Sharia Stock Index (ISSI) are attributed to macroeconomic factors. Previous research has yielded inconsistent results regarding the factors affecting ISSI price changes, primarily focusing on the short to medium-term. This study aims to investigate and evaluate the impact of macroeconomic variables on ISSI prices. The research methodology employed is a descriptive quantitative approach, utilizing secondary data sources. The Error Correction Model (ECM) is used, utilizing quarterly time series data from the 2nd quarter of 2011 to the 4th quarter of 2022. The findings indicate that over an extended period, inflation and gross domestic product are the variables that influence the price of the Indonesian Sharia Stock Index (ISSI). In the short term, only the exchange rate affects the price of ISSI. However, money supply does not have a significant impact on ISSI prices in either the long or short term. The research findings underscore the significant influence of macroeconomic variables on the Indonesian Sharia Stock Index across different time frames. These results offer valuable insights for investors and policymakers by highlighting the complex interplay of factors affecting the stock market. Further analysis of these dynamics can contribute to a more comprehensive understanding of the Indonesian financial market and assist in making well-informed investment decisions. Moreover, exploring the underlying reasons for the observed relationships between macroeconomic variables and ISSI price movements can open opportunities for proactive risk management and strategic investment planning.